Moving towards a knowledge-based economy: What is needed to enable science, technology and innovation in post-revolutionary Egypt. - El Tanany, Salma Khaled (AUC Knowledge Fountain, 2013)
The purpose of this research is to examine the current state of Science, Technology and Innovation (STI) in Egypt. Provide a careful view of the obstacles and challenges Egypt is facing in enhancing its STI system and how this is hindering Egypt’s transformation to a knowledge-based economy. Applying qualitative methods through in-depth interviews with the different experts from the field along with research conducted helped develop policy recommendations that could act as a road map that guide us in our pursuit for revolutionary transformation. The research findings indicate that the process of transformation to a knowledge-based economy is a holistic process; it requires full commitment and participation from government, policy makers and the people, it requires a vision that would unite the efforts and hard work towards achieving a certain goal to be able to reap the success of many of the exemplary attempts initiated, and requires bottom-up approach in setting the ground, changing the culture and building the right foundation that would lead us to a sustainable knowledge-based society.